Konsep Kebijakan dan Inovasi dalam Pendidikan di Indonesia Pasca Pandemi Covid-19 - Hasna Salsabila; Maharani Sartika Dewi; Patricia Bunga Juwita Galand; Vesha Nuriefer Haliza (Jurnal Ilmiah Wahana Pendidikan, 2022)
Since the outbreak of a disease called Corona Virus originating from Wuhan, China, otherwise known as COVID19, it has been reported in various aspects at the end of 2019. In this regard, the practice of applied education was still traditional education before COVID-19 reached Indonesia. Some schools have developed a culture of education through IT, especially at the elementary school level, but traditional education is still the main priority. Therefore, bypassing this section, the author wants to dig deeper into educational innovations that are involved in educational practice in the era of the COVID-19 pandemic. This study uses a literature review (books, magazines, determinations, similar to essays). Literature study is the procedure used to collect information or sources related to the subject discussed in the determination. The result of this determination is that a solution is found in the form of an innovation from government policies to education in Indonesia after the pandemic